FOP: From Biomolecules to Hope - Frederick S. Kaplan; Robert J. Pignolo (Biomolecules)
In the introduction to his 1970 textbook BIOCHEMISTRY, Albert Lehninger wrote “Living things are composed of lifeless molecules [...]